DIONÝZ ĎURIŠIN: MEĐUKNJIŽEVNE ZAJEDNICE I TEORIJA UMJETNIČKOGA PRIJEVODA (Philological Studies, 2019)
Even today, Dionýz Ďurišin’s theory of interliterary communities is one of the starting points for intercultural research of literature. Ďurišin approaches the interliterary communities and the phenomenon of special interliterary communities from different aspects, and marks out the literary translation as one of the most important literary concepts. Considering the differentiation of the literary process and interliterary reception, he is interested not only in its mediatory function but also in its cultural and social function. Emphasizing the partner relationship between the translator and the original text he stresses the creative function of the artistic translation where the translator becomes the author with his/her own poetics. That is also the reason for translation in the conditions of bilinguism/polylinguism and biliterariness/poliliterariness. Ďurišin’s conclusions and suggestions offer the possibilities for research of Slavic and middle European relationships marked with the common historical, political and cultural heritage. That is especially important in the era of globalisation of the European community and the threat of loss of identity and diversity of communities.